Characteristics of hospitalizations and emergency department visits due to generalized pustular psoriasis in the United States. (3rd October 2021) - Hanna, Maya L.; Singer, David; Bender, Shaun D.; Valdecantos, Wendell C.; Wu, Jashin J.
Abstract: Objectives: Generalized pustular psoriasis (GPP) is a rare and severe, inflammatory skin disease. GPP is characterized by recurrent flares that consist of disseminated erythematous skin rash with sterile neutrophil-filled pustules that can result in an emergency department (ED) visit or hospital stay due to systemic complications. This study characterizes hospitalizations, ED visits, and inpatient treatment due to GPP in the United States (US). Methods: A descriptive, retrospective cross-sectional analysis was conducted in Cerner Health Facts, a US electronic medical record database. Hospitalizations and ED visits were identified between 1 October 2015 and 1 July 2017. Visits were included in the study if they were GPP-related, defined as a GPP diagnosis (ICD-10-CM code: L40.1) in the first or second position at admission or discharge, and if the discharge date was within the study period. Hospitalizations and ED visits were the units of analysis. Demographics, comorbidities, medication use, and outcomes were characterized with descriptive statistics. Outcomes included length of stay, intensive care unit (ICU) admission, and death. Results: A total of 71 GPP-related hospitalizations and 64 GPP-related ED visits were included in the study. Other specified inflammatory skin conditions (OSICS)/skin and subcutaneous tissue infections (54%/34%), fluid and electrolyte disorders (46%), hypertension (30%), septicemia (24%), and acute renal failure (18%) were the most frequently coded conditions accompanying a GPP-related hospitalization. OSICS/skin and subcutaneous tissue infections (47%/42%) were the most commonly coded conditions accompanying a GPP-related ED visit. Medication use during GPP-related hospitalizations included topicals (triamcinolone (42%); clobetasol (17%)), systemic corticosteroids (prednisone (20%); methylprednisolone (11%)), and non-biologic and biologic immunosuppressants (cyclosporine (6%); methotrexate (4%); etanercept (1%)). Analgesics (acetaminophen 67%; morphine 24%), and antibiotics (vancomycin 21%) were also common. The median length of stay for hospitalizations was 5 days. Three hospitalizations included an ICU admission and two hospitalizations resulted in death. Conclusions: The presence of concurrent immune-mediated conditions, and frequent prescribing of analgesics, including opioids, illustrate the burden of GPP in patients requiring acute and inpatient care.